Analisis Alur Proses Penerimaan Pasien Rawat Inap di Rumah Sakit “X” Tahun 2015 dengan Pendekatan Lean Hospital - Dewi, Pretty Kristianti (UI Scholars Hub, 2015)
Lean hospital is lean methods used in hospitals, is a continuous effort made to eliminate waste and increase value added in patient care in hospitals. This method is very appropriate to analyze the process flow of inpatient admission in